Trade, finance, specialization and synchronization in the Asia-Pacific - Chia, Wai-Mun (2013)
In this paper, we examine the relationship between trade, finance, specialization and output synchronization of 12 Asia-Pacific economies by studying the direct and indirect effects of increasing trade and financial integration on output synchronization. Using cross-sectional data for the periods of 1984–1996 and 1999–2007, we estimate a system of equations accounting for both endogeneity and simultaneity. Our main findings suggest that: (1) trade and financial integration has direct positive effects, while specialization has direct negative effects on output correlations. An increase in the coefficient of trade intensity and the significance of financial integration is observed in the post-Crisis period. (2) Most estimated coefficients have signs consistent with the existing literature and the results remain robust under different measures of output correlation, but a notable difference is that trade and finance have sizable positive effects on specialization; however, specialization is not a driving force of trade. (3) Countries with more variance in exchange rates have less synchronized cycles.